AN ASSESSMENT OF THE EXTENT TO WHICH COMPUTERS HAVE BEEN IMPLEMENTED ON THE CURRICULUM IN MBIRE DISTRICT - MUZENDA, BY DOCTOR VERITY (IJRDO- Journal of Educational Research, 2017)
The aim of the present study is to assess the extent to which computers have been implemented in secondary schools in Mbire district. The population comprised of all the teachers from all the secondary schools in the district. The sample was made up of 220 respondents comprising of 20 heads of schools and 200 teachers randomly selected. The study employed a quantitative methodology and adopted the descriptive survey design. All the information was collected through a questionnaire. The study revealed that most schools in Mbire district did not effectively implement computer education. Most of the schools had a critical shortage of qualified computer teachers and as a result, pupils were taught by teachers who did not understand the subject themselves. It was also revealed that heads did not supervise the teaching of computers in a way that supported learning of the subject. The study recommends that the Ministry of Primary and Secondary Education should recruit computer qualified teachers and deploy them in all secondary schools. Heads should also prioritise the supervision of teaching of computer studies.